Surface Termination Dependent Work Function and Electronic Properties of Ti3C2Tx MXene - Schultz, Thorsten; Frey, Nathan C.; Hantanasirisakul, Kanit; Park, Soohyung; May, Steven J.; Shenoy, Vivek B.; Gogotsi, Yury; Koch, Norbert (Chemistry of materials, 2019)
MXenes, an emerging family of 2D transition metal carbides and nitrides, have shown promise in various applications, such as energy storage, electromagnetic interference shielding, conductive thin films, photonics, and photothermal therapy. Their metallic nature, wide range of optical absorption, and tunable surface chemistry are the key to their success in those applications. The physical properties of MXenes are known to be strongly dependent on their surface terminations. In this study, we investigated the electronic properties of Ti3C2Tx for different surface terminations, as achieved by different annealing temperatures, with the help of photoelectron spectroscopy, inverse photoelectron spectroscopy, and density functional theory calculations. We find that fluorine occupies solely the face-centered cubic adsorption site, whereas oxygen initially occupies at least two different adsorption sites, followed by a rearrangement after fluorine desorption at high annealing temperatures. The measured electronic structure of Ti3C2Tx showed strong dispersion of more than 1 eV, which we conclude to stem from Ti–O bonds by comparing it to calculated band structures. We further measured the work function of Ti3C2Tx as a function of annealing temperature and found that it is in the range of 3.9–4.8 eV, depending on the surface composition. A comparison of the experimental work function to detailed density functional theory calculations shows that the measured value is not simply an average of the work function values of uniformly terminated Ti3C2 surfaces but that the interplay between the different surface moieties and their local dipoles plays a crucial role.